The Influence of the Quantum Reading Learning Model on the Speed Reading and Reading Comprehension Skills of Fifth-Grade Students at Public Elementary School 15 Anduring, Padang City - Riche Afrina; Alfroki Martha; Ismira Ismira (FKIP - Universitas Riau, 2026)
This research examines the impact of the Quantum Reading model on the speed reading and reading comprehension skills of fifth-grade students at Public Elementary School 15 Anduring, Padang. The study used a quasi-experimental method with a Nonequivalent Control Group Design. Two classes were selected as samples: class V.C as the experimental group and class V.B as the control group, with 22 students in each. Instruments consisted of validated and reliable tests for speed reading (KPM) and reading comprehension. Data analysis involved prerequisite tests for normality and homogeneity, followed by hypothesis testing using an Independent Sample t-test.The results indicate that the Quantum Reading model significantly improved students’ reading abilities. The experimental group achieved a higher average posttest score in speed reading (147.50) compared to the control group (126.95). Similarly, in reading comprehension, the experimental group scored 23.18, surpassing the control group’s 17.95. Statistical testing showed significance at p < 0.05, meaning the alternative hypothesis was accepted. In conclusion, the Quantum Reading model is more effective than traditional approaches, helping students to read faster while also deepening their comprehension of texts.